تحليل تطبيق طريقة ﺍﻹملاء لترقية مهارة الكتابة في تعليم اللغة العربية بمدرسة الإخلاص الدينيّة الأوليّةبوربا بارو - Nila Hildayanti Batubara; Zulpina; Fadlan Masykura Setiadi (PT. Willy Print Art, 2025)
This research was conducted at MDA Al-Ikhlas Purba Baru with the aim of finding out the application of the imla' method in learning Arabic at MDA Al-Ikhlas Purba Baru, to find out the advantages and disadvantages of the imla' method in learning Arabic at MDA Al-Ikhlas Purba Baru, and to find out the solutions/problems solving the imla' method in learning Arabic at MDA Al-Ikhlas Purba Baru. This research uses a qualitative approach, namely by using observation, interviews, and documentation. While the data analysis techniques used are data checking, data grouping, data checking and data analysis. The results of this study indicate that 1) the application of the imla' method in Arabic language learning at MDA Al-Ikhlas Purba Baru after using the imla' method, students find it easier and understand to learn imla' by providing mufrodatz, namely introducing hijaiyah letters and examples of their writing, using tarjamah, and using imla' manqul. 2) the advantages and disadvantages of using the imla' method, the advantages after using the imla' method are that it trains students' hearing to be better, and by using the imla' method, teachers find it easier to monitor the class situation when carrying out learning, and the class atmosphere becomes calm. The disadvantages after using the imla' method are that students tend to be watchful, the material mastered by students is limited to only that which has been delivered by the teacher, students do not understand the material delivered by the teacher. 3) Solution or problem solving using the imla' method by means of implementing Arabic language learning, the teacher emphasizes and writes down the mufradatz, introduces the hijaiyah letters, uses translation, distributes reading texts and copies them, students re-study the reading text and then students write the reading text without looking at the text, and when using imla'.